Pyro-lytic de-oxygenation of waste cooking oil for green diesel production over Ag2O3-La2O3/AC nano-catalyst - Abdulkareem-Alsultan, G.; Asikin-Mijan, Nurul; Mansir, Nasar; Lee, Hwei Voon; Zainal, Zulkarnain; Islam, Aminul; Taufiq-Yap, Yun Hin (Elsevier, 2019)
Green diesel derived from deoxygenation technology has been developed to replace instability of fatty acid alkyl ester (biodiesel) due to the presence oxygenated species. Herein, the green diesel was synthesized via catalytic deoxygenation (DO) of waste cooking oil (WCO) over synthesized Ag2O3–La2O3/ACnano catalyst under hydrogen-free environment. Based on the study, the effect of silver (Ag) species (10–30 wt%) towards DO reactivity and product distribution was investigated. It was revealed that the Ag2O3(10%)–La2O3(20%)/ACnano formulation resulted in a higher yield (∼89%) of liquid hydrocarbons with majority of diesel fractions selectivity (n–(C15+C17) at ∼93%. In addition, decarboxylation and decarbonylation reaction processes of the WCO to DO was promoted by the presence of acid and basic active sites on Ag2O3(10%)–La2O3(20%)/ACnano catalyst. The high stability of the Ag2O3(10%)–La2O3(20%)/ACnano catalyst was proven by maintenance of six continuous runs with constant yield (>80%) of hydrocarbons and (>93%) selectivity of n–(C15+C17) under mild reaction conditions.